2017
DOI: 10.1016/j.concog.2017.06.015
|View full text |Cite
|
Sign up to set email alerts
|

“Being there” and remembering it: Presence improves memory encoding

Abstract: Few studies have investigated the link between episodic memory and presence: the feeling of "being there" and reacting to a stimulus as if it were real. We collected data from 244 participants after they had watched the movie Avengers: Age of Ultron. They answered questions about factual (details of the movie) and temporal memory (order of the scenes) about the movie, as well as their emotion experience and their sense of presence during the projection. Both higher emotion experience and sense of presence were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 71 publications
6
57
0
6
Order By: Relevance
“…Immersive technology has been a driving force in the present research since the 1990s (Steuer 1992), based on the observation that IVE users have a stronger sense of the spatial presence, compared, for example, to those of low-immersive media types such as videos or desktop applications (Seibert and Shafer 2018;Kim et al 2014). Moreover, it has been argued that an increased feeling of the presence improves the effectiveness of VR applications (e.g., as tools for learning and training, entertainment or therapy; Cummings and Bailenson 2016;Hartmann et al 2015;Makowski et al 2017). This effectiveness is considered to be particularly high when users experience the IVE from the perspective of an avatar, i.e., as a functional part of the represented environment (Bailey et al 2016).…”
Section: Spatial Presencementioning
confidence: 99%
“…Immersive technology has been a driving force in the present research since the 1990s (Steuer 1992), based on the observation that IVE users have a stronger sense of the spatial presence, compared, for example, to those of low-immersive media types such as videos or desktop applications (Seibert and Shafer 2018;Kim et al 2014). Moreover, it has been argued that an increased feeling of the presence improves the effectiveness of VR applications (e.g., as tools for learning and training, entertainment or therapy; Cummings and Bailenson 2016;Hartmann et al 2015;Makowski et al 2017). This effectiveness is considered to be particularly high when users experience the IVE from the perspective of an avatar, i.e., as a functional part of the represented environment (Bailey et al 2016).…”
Section: Spatial Presencementioning
confidence: 99%
“…However, there is now an understanding that the value of virtual reality comes from immersion and the sense of presence -the feeling of 'being there' -that it generates. 3,4 As such, only VR that is immersive -using headsets that completely block out the real world -is now referred to as 'virtual reality'.…”
mentioning
confidence: 99%
“…Therefore, as fiction and emotion are connected in everyday life, a simple process of classical conditioning might explain the tendency to classify emotional stimuli as simulations. Yet the literature taking interest in the concept of presence (the feeling of being located in the current experience and responding to it as if it was real) showed that emotions tend to increase the feeling of reality, rather than decreasing it (Baños et al, 2004;Baños et al, 2008;Makowski, Sperduti, Nicolas, & Piolino, 2017;Riva et al, 2007;Västfjäll, 2003). This apparent contradiction might be better explained by the context of ER.…”
Section: Discussionmentioning
confidence: 99%